2008
DOI: 10.1089/tea.2007.0237
|View full text |Cite
|
Sign up to set email alerts
|

Medium Flow Rate Regulates Viability and Barrier Function of Engineered Skin Substitutes in Perfusion Culture

Abstract: Perfusion culture of engineered tissues improves mass transfer of nutrients and provides flow-mediated mechanical stimulation to the developing constructs, thereby improving their anatomy and physiology in vitro. In this study, the responses to medium flow rate of engineered skin substitutes (ESS) incubated in perfusion at the air-liquid interface were investigated. ESS fabricated with autologous keratinocytes, fibroblasts, and collagen-glycosaminoglycan (GAG) sponges were incubated for 21 days at the air-liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…In contrast, the UCMC 161 medium used to culture skin (co-culture of fibroblasts and keratinocytes) was designed to promote epidermal proliferation and differentiation while maintaining fibroblast viability. Prior studies showing BrdU staining of ES culture in this medium indicated that the epidermis was highly proliferative but very few fibroblasts in the dermis were actively proliferating (Kalyanaraman et al, 2008). As the culture medium is formulated to maintain fibroblast viability and promote epidermal proliferation and differentiation, it is not surprising that dermal strength in our model was lower than that of studies that utilize DME-based mediums with FBS supplements where fibroblasts are highly proliferative and deposit large amounts of ECM.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, the UCMC 161 medium used to culture skin (co-culture of fibroblasts and keratinocytes) was designed to promote epidermal proliferation and differentiation while maintaining fibroblast viability. Prior studies showing BrdU staining of ES culture in this medium indicated that the epidermis was highly proliferative but very few fibroblasts in the dermis were actively proliferating (Kalyanaraman et al, 2008). As the culture medium is formulated to maintain fibroblast viability and promote epidermal proliferation and differentiation, it is not surprising that dermal strength in our model was lower than that of studies that utilize DME-based mediums with FBS supplements where fibroblasts are highly proliferative and deposit large amounts of ECM.…”
Section: Discussionmentioning
confidence: 88%
“…Modifying the electrospinning parameters to achieve better porosity and larger pore dimensions has also been attempted. Increased flow-rates were found to increase the pore dimensions of synthetic human elastin nanofibrous scaffolds that were found to be superior to those scaffolds fabricated using low flowrates for skin tissue engineering applications [57]. The difference in the cell response to both scaffolds was attributed to the differences in the pore dimensions.…”
Section: Scaffold Design Strategiesmentioning
confidence: 90%
“…The re-endothelialization of a porcine jejunal segment, which subsequently could be perfused through the remaining arterial connection, still represents a fundamentally different approach than our experimental setup, arguably rendering the results incomparable to our study: We use a facilitated diffusion approach without a connective vasculature. Kalyanaram et al 35 focused on the effect of flow conditions on bi-layered skin grafts without any angiogenesis occurring in vitro. They revealed that barrier function of a skin graft, cultivated in a perfused bioreactor with a 5 mL/ min flow, increases significantly.…”
Section: Discussionmentioning
confidence: 99%